Necesidad de reformar el art…5 del título v del libro segundo del código de la Niñez y Adolescencia, debido al perjuicio que la subsidiaridad en el pago de alimentos causa a la familia del progenitor (a) obligado - Salazar Vacas, Luis Alfonso (2015)
The family is the institution of greater importance within the institutions of both the State and society, being our first school at birth, as well as the mental support we received from its members in each of our activities over the life. Therefore, the importance of stability and well-being of this noble institution is protected by the state as by the law, particularly in the so-called family law, designed to protect the rights and individual well-being of both parents, children, grandparents and other components thereof. Such importance has occupied a prominent space in the various forums and workshops covering the treatment of human rights, since according to the tools that are available to the family for protection, together with the stability and compatibility of characters each of its members and the constant practice of ethical and moral values, forming whole human beings will be achieved not only in the emotional and intellectual, but also proceed to their peers. Unfortunately there are adverse situations that threaten the stability and family welfare, in some cases related to domestic violence, in others by the breakdown of the family unit because of migration or the irresponsibility of the parents to the rights and obligations of children born within the marriage, issues that today have led to other problems that have reached force in our society, that threaten the stability and welfare of the family. Before the breakup of the married couple, either by violence, misunderstanding of characters or other factors, the departure of one spouse from home occurs, a situation that affects the psychological and emotional wellbeing of both the couple and their children fruits relationship, which entails that there is already a violation both of the rights of the family, as the rights of minors, a situation which the State and the law have created legal tools, such as the so-called "pension food "which, through due process, determines the setting of a monthly economic aliquot to be covered either by the father or mother, for the investment in food, clothing and other expenses of its offshoots, which if not offset the absence of affection and personal protection, at least it ensures that the child will be their basic needs covered. Despite the importance of this tool has had for the welfare of the rights of children and adolescents, there are countless cases in which this feature-law is not met fully by the father or mother forced for that reason family law and the state had to take radical positions to monitor compliance with these obligations, going so far as to move this very personal obligation to third parties, made up of parents, siblings or other relatives of the parent, obliged to pay pensions food for their children, through corrective measures and in violation of the freedom, fair situation, especially given that the provision of food is an individual obligation, not collective, at least as determined by international law. Therefore, the development of this work is aimed at analyzing the various aspects related to the provision of food and the effects that subsidiarity in the payment of the same causes to the members of the family of the father or mother required, as well as society itself, since it is not possible to talk about building a social good living, if there are still criteria of irresponsibility within the ideology of the citizens of our nation